Fly down: design thinking auxiliando pais nos cuidados e empoderamento de crianças com síndrome de down - Campagnollo, Marieli Zen (My University, 2021)
Down syndrome is a genetic condition, and despite the technological advances, it is not possible to determine the level of independence that they can achieve in adulthood, this struggle is daily, therefore, the care exercised by family members is extremely important for their development. . This work aims to develop a research on the theme, understanding its complexity, and through studies based on design thinking, a service was proposed for parents of children with down syndrome, in which they help in their daily care, in health , offering consultations with specialists, passing on information on how they should stimulate the development of children, and which empowers them, so that they encourage their children, encouraged and believing in their abilities. [resumo fornecido pelo autor]
A síndrome de down é uma condição genética, e que apesar dos avanços tecnológicos, não é possível determinar o nível de independência que conseguem atingir na fase adulta, essa luta é diária, portanto, os cuidados exercidos pelos familiares são extremamente importantes para o seu desenvolvimento. Este trabalho tem como objetivo, desenvolver uma pesquisa sobre o tema, compreendendo a sua complexidade, e através de estudos baseados no design thinking, foi proposto um serviço para pais de crianças com síndrome de down, em que ajude nos seus cuidados diários, na saúde, oferecendo consultas com especialistas, passando informações de como devem estimular o desenvolvimento das crianças, e que os empodere, para que encorajem os filhos, incentivado e acreditando nas suas capacidades. [resumo fornecido pelo autor]
Keywords: Design; Familia; Down, Síndrome de